2021
DOI: 10.1177/1055665621990148
|View full text |Cite
|
Sign up to set email alerts
|

Dental Subphenotypes in Infants With Orofacial Clefts—A Longitudinal Population-Based Retrospective Radiographic Study of the Primary and Secondary Dentitions

Abstract: Objectives: To determine the developmental patterns of primary and secondary dentitions in infants with orofacial clefts. Design: Retrospective, longitudinal, population-based cohort study. Materials: Longitudinal records and radiographs of 192 nonsyndromic Northern European infants with isolated unilateral cleft lip (UCL, n = 111) and isolated cleft palate (CP, n = 81). Methods: Radiographic assessments of primary and secondary dentition anomalies and dental maturation, by gender and cleft severity for compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…This finding is different from the results of Berkowitz et al, 29 who reported that the alveolar cleft occurs between the canine and lateral incisor, but consistent with the findings of Tsai et al 30 We suspect this is likely due to the maxillary lateral incisor being a composite tooth formed from the fusion of 2 dental epithelia. 31 Degeneration of the dental epithelium in the medial nasal process causes lateral incisors to appear at the distal side of the cleft, and degeneration in both processes causes tooth agenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is different from the results of Berkowitz et al, 29 who reported that the alveolar cleft occurs between the canine and lateral incisor, but consistent with the findings of Tsai et al 30 We suspect this is likely due to the maxillary lateral incisor being a composite tooth formed from the fusion of 2 dental epithelia. 31 Degeneration of the dental epithelium in the medial nasal process causes lateral incisors to appear at the distal side of the cleft, and degeneration in both processes causes tooth agenesis.…”
Section: Discussionmentioning
confidence: 99%